2015
DOI: 10.1016/j.jecp.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reading proficiency on embedded stem priming in primary school children

Abstract: Prior evidence from masked morphological priming has revealed conflicting findings regarding the acquisition of morpho-orthographic segmentation mechanisms in developing readers. Here, we examined changes in masked morphological priming across grade within a large sample of French primary school children (n = 191, Grades 2-5) and how these effects are modulated by individual differences in reading proficiency, spelling proficiency, and morphological awareness. Target words were preceded by either (a) a suffixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 23 publications
6
44
2
1
Order By: Relevance
“…Importantly, in contrast to adults, the difference between the suffixed and nonsuffixed prime conditions did not reach significance in developing readers, which suggests that there was no evidence for morpho-orthographic decomposition by means of affix-stripping in these individuals. Presumably, elementary school children instead activate embedded stems through partially shared orthography, as Beyersmann et al ( 2015b ) reported for proficient child readers. This is consistent with the pattern observed in the quantiles, suggesting that there was a shift rather than a skew in the RT distribution of the suffixed word, suffixed nonword, and non-suffixed nonword conditions.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Importantly, in contrast to adults, the difference between the suffixed and nonsuffixed prime conditions did not reach significance in developing readers, which suggests that there was no evidence for morpho-orthographic decomposition by means of affix-stripping in these individuals. Presumably, elementary school children instead activate embedded stems through partially shared orthography, as Beyersmann et al ( 2015b ) reported for proficient child readers. This is consistent with the pattern observed in the quantiles, suggesting that there was a shift rather than a skew in the RT distribution of the suffixed word, suffixed nonword, and non-suffixed nonword conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Embedded stems are mapped onto orthographic whole-word representations, even if the overlap is only partial (see also Ziegler et al, 2014 ). Embedded stems might thus function as lexical representations that can be activated automatically during the early stages of visual word recognition (Beyersmann et al, 2015b ). In a transparent language like German, where an alphabetic reading strategy is usually accurate and efficient, elementary school children could still be prone to read sequentially from left to right.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 It is likely that children also develop increased sensitivity to morphological complexities and regularities, allowing them to capitalise on the relationships between a word's morphological structure and its spelling. [18][19][20] Clearly, something develops as children move from novice to expert, and while this has its roots in phonological decoding, much more research on the development of orthographic expertise is needed. 10 READING EXPERIENCE AND THE DEVELOPMENT OF LEXICAL QUALITY Perfetti's lexical quality hypothesis 6,21 defines lexical quality as the extent to which a word's mental representation specifies its spelling, sound and meaning.…”
mentioning
confidence: 99%